ANALISIS PENYEDIAAN FASILITAS EQUIPMENT STORAGE AREA GUNA MENCIPTAKAN SAFETY FLOW GROUND SUPPORT EQUIPMENT (GSE) DI BANDAR UDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Thufail Rizqi Nur Hilal; Elfi Amir; Dian Anggraini Purwaningtyas (Jurnal Teknologi Kedirgantaraan, 2026)
This research analyzes the provision of Equipment Storage Area (ESA) facilities to create a safe flow for Ground Support Equipment (GSE) at Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan International Airport, given the increase in flight operations and the need for optimal ground handling. The main problems identified are the absence of clear markings in Storage B to indicate storage boundaries and the irregular layout of GSE. Using a qualitative descriptive method involving observation, interviews, and documentation in the airport's equipment storage area, the results indicate that Storage B does not meet operational safety standards due to the absence of markings, leading to unclear boundaries and disorganized GSE layout, which could hinder service delivery and reduce the safety and efficiency of GSE operations. As an improvement effort, it is strongly recommended to create clear storage markings in Storage B in accordance with the Director General of Civil Aviation Decision No. PR 21 of 2023, as well as to design a systematic GSE layout. This implementation aims to organize parking positions, improve land efficiency, prevent overlapping access routes, and ensure safer and more efficient ESA management in accordance with applicable regulations.